Qualitative Examination Of Amfetamine And Ephedrine In Urine In Doping Using Gas Chromatography-Mass Spectrometry Method - Kusmiyati, Mimin; Trinovani , Elvi; Sudaryat , Yayat; Bakhtiar , Dicky (Jurnal EduHealth, 2022)
Amphetamines and ephedrine are stimulant class doping drugs which have the effect of reducing fatigue and drowsiness, increasing alertness, physical strength, mental sense of competition and competitive attitude. Analysis of doping drugs in urine that has been recommended by the International Olympic Committee, including Gas Chromatography-Mass Spectrometry. Derivatization is carried out to change the polarity of the analyte, making it easier to become a gas and stable to heating. This study was conducted for qualitative analysis of amphetamine and ephedrine, using an HP5MS column containing non-polar phenyl methyl siloxane, temperature 100-250oC with a temperature increase of 10oC/minute. Then it was extracted with a mixture of diethyl ether-ethylacetate (1:1) in an alkaline medium pH 8, the organic layer was evaporated then derivatized with trifluoro-acetic acid-anhydride and ephedrine with acetic-anhydride-pyridine (3:2). The final results showed that the retention times of amphetamine and ephedrine were 10.47 and 4.9 minutes. While the derivatives are 13.34 and 5.50 minutes. Identification using mass spectrometry for each compound showed that the mass spectra matched the Ref. and the amphetamine and ephedrine structural similarity index was 96% and the detection limit for each compound was 2 ug/ml.